Atividade elétrica muscular, funcionalidade de membros superiores e dor em mulheres mastectomizadas com e sem reconstrução mamária - Godoy, Alessandra Sartori (2017)
This study aimed to evaluate the muscular electrical activity of the shoulder complex, upper limb function and pain in women undergoing mastectomy with and without breast reconstruction. For this, a control case study was carried out, in which 24 women who underwent unilateral modified radical mastectomy surgery were evaluated. Participants were in the age range of 29 to 70 years, with surgery time of ninety days to five years and should have completed adjuvant therapy for at least three months. They were divided into 2 groups: mastectomy group without breast reconstruction (MR group, n = 12) and group with breast reconstruction (IBR group, n = 12). Exclusion criteria were: presence of lymphedema; musculoskeletal or nerve disorders of the upper limb, diagnosed prior to the onset of breast cancer; unable to perform the tests (by limitation of range of motion or severe pain); pacemakers; obesity; allergy to adhesive material; signs of active infection. This work was approved by the Ethics Committee on Human Research at UFSM (CAAE nº: 52451215.0.0000.5346) and all the participants signed the Free and Informed Consent Term. They were evaluated for the EMG activity of the pectoralis major (PM), middle deltoid (MD), upper trapezius (UT), middle trapezius (MT), lower trapezius (LT) during two tasks (sagittal plane functional task , called shelf reach and elevation of the shoulder in the scapular plane). Upper limb function (through the DASH questionnaire) and intensity of shoulder pain (through VAS) were also evaluated. Greater EMG activity was found in the CR group for MT muscles (p = 0.017) and LT (p <0.001). Upper limb function and pain did not differ between groups (p> 0.05). There were some positive, moderate-to-strong correlations between EMG activity versus pain, EMG activity versus upper limb function and pain versus upper limb function. Immediate breast reconstruction after mastectomy influences the increase in EMG activity of MT and LT muscles. It is suggested that to maintain its functional activities there is MT compensation to stabilize the scapula and allow normal movement of the shoulder complex. There is a relationship of the EMG activity of some muscles of the shoulder complex with pain and functionality.